Maintaining the Mandailing Mengalap Boru Custom in the Current Era of Modernization in Pematang Simalungun Village, Siantar District, Simalungun Regency - Ritonga, Rayhan Aulia Annisa; Dora, Nuriza (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the tradition of eating boru in the Pematang Simalungun Village, Siantar District, Simalungun Regency. This tradition of menggalap boru is a tradition that has existed for a long time, where this tradition is that the husband is obliged to give a certain amount of money and cloth to his wife's namboru children at the time of walimatul'urs (the wife's departure party for her husband's place) as a request for permission for the wife's namboru children. This tradition of processing boru is a condition for the marriage to be considered valid by Mandailing customs. This research uses a qualitative approach with ethnographic methods. Data collection techniques in this research are observation, interviews and documentation. The aim of this research is to explore and examine the new melap tradition in the Mandailing custom in Pematang Simalungun Village. The results of this research are to find out how Mandailing customs are used in traditional Mandailing wedding ceremonies in Pematang Simalungun Village.